Prospering the ASEAN Community: How Micro-Region Becomes a Driving Force Prosperity in Indonesia’s Border Area? - Fitrisia Munir; Yanyan Mohammad Yani; Rendi Prayuda; Artha Yudilla; Dini Tiara Sasmi (Jurnal Hubungan Internasional, 2023)
Providing space for sub-state actors’ actions at the micro-regional level is a significant trend in advancing regional integration in ASEAN. Transnational activities have contributed to the trade development and optimization of each country’s local production, a strategic goal, and micro-regions have emerged as critical players in this activity. Regional integration will be localized if sub-state actors play a significant role and engage in smaller regionalism activities, such as in border areas. With the goal of encouraging prosperity and reducing development gaps, especially for people in border areas, this research examined the collaboration of sub-state actors across ASEAN countries as an alternative development paradigm. Alternative research hypotheses applicable in various scientific disciplines were included in this research through a qualitative analysis method and a reflective case study approach. This research focused on the roles and activities of sub-state actors in border areas such as the Riau Islands with Malaysia and Singapore, who could work hard together with other sub-state actor entities through the support of a strong leadership network to take quicker and more efficient actions to overcome various issues. This research strengthens the existing literature by discovering that the collaboration of sub-state actors between countries in the border region has played a big role in encouraging the border community to advance and compete in the international arena, and ASEAN has become an institution encouraging and guaranteeing equal development for people in the border areas.